KOMUNIKASI PENYULUHAN DAN ADOPSI INOVASI - Dayana Flora K. Sinurat (PERSPEKTIF, 2012)
The Title of this research is Counseling Communication and Adoption of Innovation (Correlational Studies of Counseling Communication of Cervical Cancer by PKBI Sumatera Utara Concerning the Level Woman’s Adoption of Innovation at Kelurahan Belawan II). The aim of this study is to determine the effect of conceling cervical cancer that conducted by PKBI Sumatera Utara concerning the level of woman adoption of innovation at Kelurahan Belawan II in form of pap smear test. This study uses total sampling with the total population are 17 people. The data are gotten from questioner with number of questions are 34 questions. Data obtained were analyzed by using analysis of single table and cross table. Processing analysis data using SPSS for windows version 15.0. Hypothesis results showed there was significant correlation between counceling communication of cervical cancer by PKBI Sumatera Utara concerning the level of woman’s adoption of innovation at Kelurahan Belawan II.